Pharmacy Practice and Education in Austria - Thierry Langer; Helmut Spreitzer; Teresa Ditfurth; Gunar Stemer; Jeffrey Atkinson (MDPI AG, 2018)
The PHARMINE (“Pharmacy Education in Europe”) project studied pharmacy practice and education in the European Union (EU) member states. The work was carried out using an electronic survey sent to chosen pharmacy representatives. The surveys of the individual member states are now being published as reference documents for students and staff interested in research on pharmacy education in the EU and in mobility. This paper presents the results of the PHARMINE survey on pharmacy practice and education in Austria. In the light of this, we examine the harmonisation of practice and education in Austria with EU norms.